1996
DOI: 10.1046/j.1471-4159.1996.66062621.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation of Human Serotonin Transporter Gene Expression

Abstract: Mood, emotion, cognition, and motor functions as well as circadian and neuroendocrine rhythms, including food intake, sleep, and reproductive activity, are modulated by the midbrain raphe serotonin (5‐HT) system. By directing the magnitude and duration of postsynaptic responses, carrier‐facilitated 5‐HT transport into and release from the presynaptic neuron are essential for the fine tuning of serotonergic neurotransmission. Interest in the mechanism of environmental factor‐, disease‐, and therapy‐induced modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,346
6
42

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,074 publications
(1,410 citation statements)
references
References 11 publications
16
1,346
6
42
Order By: Relevance
“…65 Several polymorphisms in the SLC6A4 gene have been described, including a variable number tandem repeat in exon 2, 66 a restriction fragment-length polymorphism in the 3 0 untranslated region, 67 and a variable number tandem repeat polymorphism in the 5 0 promotor region, termed the 5-HTT gene-linked polymorphic region (5-HTTLPR). 68 The 5-HTTLPR has two common alleles: a 'long' (l) allele with 16 imperfect repeats of an approximately 22-base-pair element and a 'short' (s) allele with 14 repeats.…”
Section: -Httlpr Long and Short Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Several polymorphisms in the SLC6A4 gene have been described, including a variable number tandem repeat in exon 2, 66 a restriction fragment-length polymorphism in the 3 0 untranslated region, 67 and a variable number tandem repeat polymorphism in the 5 0 promotor region, termed the 5-HTT gene-linked polymorphic region (5-HTTLPR). 68 The 5-HTTLPR has two common alleles: a 'long' (l) allele with 16 imperfect repeats of an approximately 22-base-pair element and a 'short' (s) allele with 14 repeats.…”
Section: -Httlpr Long and Short Allelesmentioning
confidence: 99%
“…68,[70][71][72][73] However, the translation of in vitro findings into in vivo functioning does not appear straightforward. Human neuroimaging studies of 5-HTT availability [74][75][76][77][78][79] and post-mortem studies of 5-HTT bindings and rRNA expression [80][81][82] have not detected any consistent effect of 5-HTTLPR.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…The most common assessed variants are a deletion/ insertion polymorphism in the transcriptional control region of the SLC6A4 gene with functional effects (5HTTLPR) [227][228][229] and a variable number of tandem repeat in intron 2 (STin2). Several studies have found an association of the short alleles of 5HTTLPR with AD, 217,[230][231][232][233] fewer studies of the long alleles.…”
Section: Chromosome 17mentioning
confidence: 99%
“…17 The 5-HTTLPR was genotyped using PCR amplification. 18 To determine if there were any differences in nongenotype confounds between the genotype groups, one-way ANOVA and w 2 tests were used.…”
Section: Subjectsmentioning
confidence: 99%